THE USE OF ENGLISH VIDEO LEARNING IN INSTAGRAM REELS TO IMPROVE STUDENTS’ VOCABULARY MASTERY AT SMK GEMA NUSANTARA - Meynata, Esa; Purwanto, Buntara Adi (Language and Literature Faculty, Universitas Sains Al-Qur'an (UNSIQ) Jawa Tengah di Wonosobo, 2025)
This study explores the use of English video learning on Instagram Reels to improve students' vocabulary mastery at SMK Gema Nusantara. Employing a qualitative research method, the study focuses on understanding students’ experiences, perceptions, and challenges when engaging with Instagram Reels as a learning tool. Data were collected through observations, interviews, and document analysis involving 15 students selected via purposive sampling. Thematic analysis was applied to identify recurring patterns and insights from the data. The findings indicate that students found Instagram Reels to be an engaging and relatable platform for learning English vocabulary. The visual and auditory elements of short videos helped students retain new words more effectively. Moreover, the interactive and entertaining nature of Instagram Reels increased students’ motivation and reduced anxiety associated with traditional learning methods. However, some challenges, such as internet accessibility and content selection, were noted. The study concludes that Instagram Reels has the potential to enhance vocabulary mastery when thoughtfully integrated into the learning process. Teachers are encouraged to curate or create relevant content and guide students in using digital platforms responsibly to optimize learning outcomes.